2011
DOI: 10.1111/j.1600-0412.2011.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood ratios for the prediction of preterm delivery with biomarkers

Abstract: Several biomarkers have been identified for assessment of risk of preterm delivery. Their clinical relevance depends on the efficacy of the interventions which can be offered to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 106 publications
1
18
0
Order By: Relevance
“…Similarly, it has been noted that for a fixed false positive rate of 10%, maternal characteristics and obstetrical history have a sensitivity of 27.5% for preterm birth with an AUC of 0.61 (0.57–0.65) . This stands in contrast to the results of combined testing with AFP, hCG, estriol, and Inhibin A, which has a LR+ of 5.5 (5.3–5.8) for preterm birth prior to 37 weeks . This study showed that using a high cut‐off threshold for a serum marker substantially enhanced the LR+.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similarly, it has been noted that for a fixed false positive rate of 10%, maternal characteristics and obstetrical history have a sensitivity of 27.5% for preterm birth with an AUC of 0.61 (0.57–0.65) . This stands in contrast to the results of combined testing with AFP, hCG, estriol, and Inhibin A, which has a LR+ of 5.5 (5.3–5.8) for preterm birth prior to 37 weeks . This study showed that using a high cut‐off threshold for a serum marker substantially enhanced the LR+.…”
Section: Discussionsupporting
confidence: 61%
“…While the prediction of obstetrical risk using maternal serum markers is suboptimal, clinical risk factors used to determine obstetrical risk also fail to meet the standards required for risk/ prognosis setting, as generally an LR + ≥10 is considered to characterize a clinically useful test. 24 For example, a history of prior preterm birth is a commonly recognized risk factor for preterm birth in a subsequent pregnancy, yet this factor only has an LR+ of 3. 24 Similarly, it has been noted that for a fixed false positive rate of 10%, maternal characteristics and obstetrical history have a sensitivity of 27.5% for preterm birth with an AUC of 0.61 (0.57-0.65).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Conde-Agudelo and colleagues (44) and Hee (45) systematically reviewed the prediction of PTB by various biomarkers, including peripheral, cervicovaginal, and amniotic fluid levels of C-reactive protein (CRP), IL-6, IL-8, TNF-α, IL-2, IL-10, and MMP-8. Only elevated amniotic fluid MMP-8 (likelihood ratio [LR]+ 40) (44) and serum TNF-α (LR+ 10) (45) were associated with substantial increases in the likelihood of PTB. While these findings lend support to the theory that an inflammatory cascade is involved in the initiation of spontaneous preterm labor, several factors prohibit the use of these biomarkers among general clinical populations.…”
Section: The Hypothesismentioning
confidence: 99%
“…Therefore, an accurate diagnostic PTL test, which could stratify the risk, is crucial and would avoid unnecessary hospital admissions and therapies. Multiple tests aiming to identify women at risk of PTB have been proposed . Measurement of the cervical length (CL), fetal fibronectin testing, or a combination of both are useful in determining women at high risk for PTB.…”
Section: Introductionmentioning
confidence: 99%